The Book of Storms - Hatfield, Ruth (Hatfield, Ruth. Book of Storms trilogy, 2015)
When his parents disappear after a fierce storm, eleven-year-old Danny, unaccustomed to acts of bravery, comes to their rescue after finding a valuable shard of wood that enables him to talk to plants and animals and battle terrifyingly powerful enemies, including the demonic Sammael.